FRI0335 THE EFFECT OF TOFACITINIB ON RESIDUAL PAIN IN PATIENTS WITH PSORIATIC ARTHRITIS. (2nd June 2020) - Dougados, M.; Van der Heijde, D.; Bingham, C.; Taylor, P. C.; Fallon, L.; Woolcott, J.; Brault, Y.; Wang, L.; Kessouri, M.
Abstract : Background: Current treatments for PsA have proven effective in reducing patient (pt)-reported pain; 1, 2 however, residual pain often remains. Tofacitinib is an oral Janus kinase inhibitor for the treatment of PsA. Objectives: This descriptive analysis evaluated the effect of tofacitinib, adalimumab and placebo on residual pain in pts with PsA whose inflammation was attenuated after 3 months of therapy. Methods: Data were included from OPAL Broaden (NCT01877668 ), a randomised, double-blind, placebo-controlled Phase 3 trial of 12 months' duration in pts with PsA. 3 Pts were randomised to receive tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID, adalimumab 40 mg subcutaneous injection once every 2 weeks or placebo. This analysis assessed pts with 'residual pain' at Month (M)3. Residual pain was considered as pain in pts with complete attenuation of inflammation at M3, defined by a swollen joint count (SJC) of 0 and CRP levels <6 mg/L. Pain was measured by a visual analogue scale (VAS; 0 ["no pain"] – 100 mm ["most severe pain"]). Changes in pain from baseline to M3 and residual pain (VAS pain reported at M3) were assessed. Results: Demographics and baseline disease characteristics have previously been reported in the primary study, and were generally similar between treatment groups. 3 At M3, 100/422 (23.7%) pts with PsA had achieved SJC of 0 and CRP <6 mg/L. At M3, more tofacitinib-treated (tofacitinib 5 mg BID, n=23/107 [21.5%]; tofacitinib 10 mg BID, n=33/104 [31.7%]) and adalimumab-treated pts (n=31/106 [29.2%]) achieved SJC of 0 and CRP <6 mg/L vs placebo (PsA: n=13/105 [12.4%]). Baseline pain appeared numerically higher in tofacitinib-treated pts (tofacitinib 5 mg BID, 54.7 mm; tofacitinib 10 mg BID, 58.4 mm) vs adalimumab-treated pts (47.7 mm) and placebo (50.4 mm). In pts who achieved SJC of 0 and CRP <6 mg/L at M3, improvements in pain from baseline to M3 appeared numerically greater in pts receiving tofacitinib vs those receiving placebo (Figure 1a ). When considering absolute (residual) pain at M3, mean residual pain was similar across treatment groups (ranging from 22.7–29.2 mm; Figure 1b ), despite a higher baseline pain in tofacitinib treatment groups. Conclusion: Changes from baseline in pain and absolute pain at M3 suggest that in pts with PsA whose inflammation has been completely attenuated, tofacitinib might have an effect on residual pain not obviously attributable to inflammation. However, the sample population was small, and there were large standard deviations. To confirm these results and to understand the mechanisms by which tofacitinib may improve residual pain, a meta-analysis will be performed using individual participant data from pts with rheumatic disease who have participated in tofacitinib randomised controlled trials. References: [1]Gladman et al. Ann Rheum Dis 2007;66:163-68. [2]Gladman et al. Arthritis Care Res 2014;66:1085-92. [3]Mease et al. NEJM 2017;377:1537-50. Acknowledgments: Study sponsored by Pfizer Inc. Medical writing support was provided by Mark Bennett of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Maxime Dougados Grant/research support from: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Consultant of: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Speakers bureau: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV, Clifton Bingham Grant/research support from: Bristol-Myers Squibb, Consultant of: Bristol-Myers Squibb, Peter C. Taylor Grant/research support from: Celgene, Eli Lilly and Company, Galapagos, and Gilead, Consultant of: AbbVie, Biogen, Eli Lilly and Company, Fresenius, Galapagos, Gilead, GlaxoSmithKline, Janssen, Nordic Pharma, Pfizer Roche, and UCB, Lara Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, John Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Yves Brault Shareholder of: Pfizer France, Employee of: Pfizer France, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Meriem Kessouri Shareholder of: Pfizer France, Employee of: Pfizer France